Association of the Geriatric Nutritional Risk Index With the Survival of Patients With Non–Small Cell Lung Cancer After Nivolumab Therapy. Issue 2 (February 2022) - Karayama, Masato; Inoue, Yusuke; Yoshimura, Katsuhiro; Hozumi, Hironao; Suzuki, Yuzo; Furuhashi, Kazuki; Fujisawa, Tomoyuki; Enomoto, Noriyuki; Nakamura, Yutaro; Inui, Naoki; Suda, Takafumi
Abstract : The nutritional status has the potential to affect cancer immunity. We evaluated the relationship between the nutritional status and the efficacy of nivolumab in patients with non–small cell lung cancer (NSCLC). This study was a post hoc analysis of a prospective, multicenter cohort study conducted at 14 institutions in Japan between July 2016 and December 2018. The Geriatric Nutritional Risk Index (GNRI), calculated from body weight and serum albumin, was evaluated in 158 patients with NSCLC who received nivolumab. GNRI was graded as low, moderate, and high. Low GNRI was associated with significantly shorter progression-free survival [median, 1.9 mo; 95% confidence interval (CI)=0.6–3.3 mo] than moderate (median, 4.0 mo; 95% CI=2.3–5.8 mo; P =0.017) and high GNRI (median, 3.0 mo; 95% CI=1.9–7.2 mo; P =0.014). Low GNRI was also linked to significantly shorter overall survival (OS) (median, 7.8 mo; 95% CI=2.6–12.0 mo) than moderate (median, 13.0 mo; 95% CI=9.6–15.2 mo; P =0.006) and high GNRI (median, 20.6 mo; 95% CI=15.6 mo–not reached; P <0.001). High GNRI was associated with significantly longer OS than moderate GNRI ( P =0.015). In multivariate Cox proportional hazard analyses, increased GNRI was predictive of longer progression-free survival and OS, similarly as tumor programmed cell death-ligand 1 expression. In patients with NSCLC receiving nivolumab. GNRI was predictive of survival and may be useful for predicting the efficacy of immune checkpoint inhibitor therapy. Abstract : Supplemental Digital Content is available in the text.